From pre-service to practice: A narrative inquiry into differentiated instruction in Indonesian teacher education - Muthiah, Ranidya Ayu; Vianty, Machdalena; Amrullah, Amrullah (UPT Bahasa Universitas Tanjungpura, 2025)
In contemporary Indonesian education, Differentiated Instruction (DI) has become an integral component of the national curriculum and a key element of the Pre-service Teacher Professional Development Programme (PTPDP), known locally as Pendidikan Profesi Guru Prajabatan (PPG Prajabatan). This study explores how DI is understood and enacted by an alumna of a university-based PTPDP who now serves as a novice homeroom teacher and contract-based civil servant (Pegawai Pemerintah dengan Perjanjian Kerja, PPPK). Employing a qualitative narrative inquiry design, data were collected through three rounds of in-depth interviews and analysed thematically. The narrative revealed two complementary perspectives: the participant’s experience of implementing DI during her teaching practicum in a senior high school in Palembang City and her current practice in a rural elementary school. Findings show that DI fosters inclusive and responsive teaching by enabling the teacher to adapt content, process, and learning environments to students’ varying readiness and interests. However, the participant’s transition from pre-service to professional teaching also highlighted persistent challenges, particularly in content differentiation and limited school resources. The study concludes that DI not only enhances learner engagement and equity but also strengthens teachers’ professional growth, adaptability, and reflective capacity. Its contribution lies in offering an authentic account of how teacher education principles evolve into practice across diverse educational contexts in Indonesia. How to cite this paper: Muthiah, R.A., Vianty, M., Amrullah. (2025). From pre-service to practice: A narrative inquiry into differentiated instruction in Indonesian teacher education. Jourmal of Emglish Lamguage Teachimg Imnovations amd Materirals (Jeltim), 7(2), 60-79. http://dx.doi.org/10.26418/jeltim.v7i2.88936